Comparison of First-Pass Effect in Aspiration vs. Stent-Retriever for Acute Intracranial ICA Occlusion - Hernández, David; Serrano, Elena; Molins, Gemma; Zarco, Federico; Chirife, Oscar; Werner, Mariano; Lara, Blanca; Ramos, Anna; Llull, Laura; Requena, Manuel; Cuevas, Marta de Dios las; Remollo, Sebastián; et al. (Frontiers in Neurology, 2022)
The purpose of this study is to evaluate the best endovascular approach (aspiration or stent-retriever) and the impact of stent retriever size and length on clinical and angiographic outcomes in patients with acute intracranial ICA occlusion. We conducted a retrospective analysis of a prospective database of consecutive patients with acute intracranial ICA occlusion undergoing endovascular treatment in four Comprehensive Stroke Center between June-2019 and December-2020. We include 121 patients; Stent-retriever (SR) was used as first technical approach in 107 patients (88.4%) and aspiration was used in 14 patients (11.6%). SR group had higher rate of FPE compared to aspiration group (29 vs. 0%, p = 0.02). In SR subgroup, treatment highlighted higher FPE in the 6 × 50 SR (37.7%), than in the rest of the SR which are 21.2% (4–5 mm size and 20–50 mm length SR) and 19% (6 mm size and 25–40 mm length SR), but it was not found to be statistically significant. There were no other significant differences across the groups regarding primary angiographic or clinical outcomes. In our intracranial ICA occlusion series, stent retrievers were superior to direct aspiration in obtaining FPEs and mFPEs, and longer devices achieved better results with no statistically significant difference. Further studies evaluating the effects of different ICA clot removal approaches are warranted to confirm these results.